Single block costal cartilage graft in rhinoplasty Enxerto de cartilagem costal em monobloco na rinoplastia - Daniel Dias Lopes; Bruno Gazire de Araújo Andrade; Michel Luciano Holger Toledano Vaena; Denise Salles Coelho da Mota (Revista Brasileira de Cirurgia Plástica, 2011)
INTRODUCTION: It is often necessary to use inclusion materials in rhinoplasty for nose restructuring. The costal cartilage graft is one of the inclusion material options, and its use is indicated when septal cartilage is not available or is not sufficient to provide necessary remodeling of the nose. METHODS: Four patients who, for diverse reasons, had saddle nose or poor projection of the nasal dorsum underwent rhinoplasty. All received a costal cartilage graft carved in an "L" shape. The long branch of the "L" was used to reconstruct the dorsum and the short branch was used to support the new dorsum and the columella, repositioning the nasal tip. RESULTS: All patients had a good postoperative evolution and had no significant complications. There was a clear reconstruction of the dorsum and harmonization of the nasal tip. The results were as expected and were long-lasting. CONCLUSIONS: The use of a costal cartilage graft carved in a single block in rhinoplasty provides enhancement of the nasal dorsum and tip projection, promoting appropriate nasal remodeling INTRODUÇÃO: Na rinoplastia frequentemente é necessário o uso de materiais de inclusão para que se obtenha a reestruturação nasal. O enxerto de cartilagem costal é uma das opções e tem seu uso indicado quando a cartilagem septal não está disponível ou não é suficiente para promover o necessário remodelamento nasal. MÉTODO: Quatro pacientes que, por motivos diversos, apresentavam nariz em sela ou dorso nasal pouco projetado foram submetidos a rinoplastia. Todos receberam enxerto de cartilagem costal esculpido em formato de "L". O ramo longo do "L" teve como objetivo reconstituir o dorso e o ramo curto, dar suporte ao novo dorso e à columela, reposicionando a ponta nasal. RESULTADOS: Todos os pacientes evoluíram bem no pós-operatório e não apresentaram complicação significativa. Houve nítida reconstituição do dorso e harmonização da ponta do nariz. Os resultados mostraram-se previsíveis e duradouros. CONCLUSÕES: O emprego de enxerto de cartilagem costal esculpido em monobloco na rinoplastia proporciona ganho de projeção do dorso e da ponta nasais, promovendo adequado remodelamento nasal